An 'imperial radiation': Experimental and theoretical investigations of the photo-induced luminescence properties of 6, 6′-dibromoindigo (Tyrian purple). (January 2019) - Verri, Giovanni; de Fonjaudran, Charlotte Martin; Acocella, Angela; Accorsi, Gianluca; Comelli, Daniela; D'Andrea, Cosimo; Nevin, Austin; Zerbetto, Francesco; Saunders, David
Abstract: 6, 6′-dibromoindigo (DBI) is the main component of Tyrian purple, or Imperial purple, one of the most controversial, sought-after and expensive colouring matters of antiquity. Evidence of its use, both as a pigment and as a dye, is found in the archaeological record, especially in the countries surrounding the Mediterranean basin. The photo-induced luminescence properties of a synthetic sample of DBI were studied in this paper. Time-Dependent Density Functional theory (TD-DFT) was used to predict and rationalise the optical absorption and emission properties of DBI in DMSO and compared with the experimental data. The emission properties of the solid-state sample were characterised for the first time. DBI shows an emission maximum in the infrared range, at about 870 nm, and lifetime in the picosecond range. The spatial distribution of the photo-induced luminescence emission could also be recorded using a commercial infrared-sensitive camera, opening up the possibility of non-invasively investigating the use of DBI on historical artefacts.